Pengaruh Kompetensi, Independensi, dan Profesionalisme Auditor Terhadap Kualitas Audit: Studi KAP KKSP - Lestari, Ajeng Dewi; Ardiami, Kinanthi Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this study, the KAP KKSP aims to examine the effect of auditor competence, auditor independence, and auditor professionalism on audit quality. Quantitative data is the type of research used in this study. Auditors who have audited clients with the ATLAS program or who have made an Examination Working Paper (KKP) are recorded as still working and apprenticing at KAP KKSP as the population of this study. 35 participants participated in this study as respondents, and saturated sampling was the sampling method used. Using a questionnaire is one method of collecting research data. Multiple linear regression analysis has been used as a data analysis method, with audit quality as the dependent variable and competence, independence, and professionalism as the independent variables. The results showed that audit quality was positively and significantly influenced by auditor independence, audit quality was positively and significantly influenced by auditor competence, and audit quality was positively and significantly influenced by auditor professionalism. Keywords: competence, independence, auditor professionalism, audit quality.